Slang Words In Fast Five Movie - Jyhan Laraz Satrya M.; Ni Made Suwari Antari; Putu Ayu Asty Senja Pratiwi (Peneliti.net, 2026)
This undergraduate thesis, Slang Words in Fast Five Movie, investigates the use of slang in the film Fast Five. It focuses on two main objectives: classifying the types of slang used and analyzing their meanings. Chapman’s theory is applied to categorize slang into Primary and Secondary types, while Leech’s theory of meaning supports interpreting these slang expressions. This combined framework explores slang’s linguistic and cultural roles in informal cinematic dialogue.Data collection was conducted through documentation. The researcher watched Fast Five multiple times to understand the storyline, characters, and dialogue. The movie script served as a textual reference to identify slang precisely. Selected slang words were informal and nonstandard, documented with contextual details such as speaker, scene, and emotional tone. This approach facilitated a systematic analysis of slang functions and meanings within the film. The study identifies all types of slang outlined in Chapman’s theory, including both Primary and Secondary slang, reflecting diverse informal expressions among characters in Fast Five. Using Leech’s theory, six of the seven meaning types, conceptual, connotative, affective, social, reflected, and collocative, are found. In contrast, thematic meaning is absent, likely because the film prioritizes fast-paced action over symbolic narrative. Slang use aligns with the film’s urban, multicultural context, reinforcing character identity, emotional tone, and social relationships. The findings show that slang in Fast Five adds realism and authenticity, while serving as a linguistic tool to express social status, cultural identity, and subtle emotions within informal speech.